Genre and Attitude to Support Character Development in Children Stories - Santosa, Riyadi; Djatmika, Djatmika; Khrisna, Dyah Ayu Nila (Register Journal, 2021)
This paper examines how character development is analyzed through attitude, genre’s stages, and phases in children's stories. Relying on ten children's stories purposively selected from two children's storybooks, the results show that all ten stories are written as narratives with a number of absences of attitude, stages, and phases of the narrative genre. most stories succeed to fulfill the obligatory stages of narrative: orientation, complication, evaluation, and resolution, even others add the optional stage, coda. However, a number of stories fail to satisfy the presence of evaluation. in addition, all stories do not exploit attitude in every phase of every stage of the narrative. Even, a number of stories miss exploiting Attitude in a number of prominent phases such as introducing the character in orientation, development, and peak of the conflict in complication, and plan and act in resolution. Besides, all ten stories do not explore all types of attitude and their sub-classifications, in which each type will contribute to the holistic description of the character. Thus, although all stories can be considered to develop character along the obligatory stages of the narrative genre, they still fail to build a more complex character development through positive-negative-positive evaluation through stages and phases of the stories.Keywords: character development; genre; stages; phases; attitude